1994
DOI: 10.1111/j.1475-1313.1994.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of past and present techniques of measuring corneal topography

Abstract: Various methods of measuring corneal topography are described. The advantages and disadvantages of the principles used in the measurement of corneal shape by the various techniques are discussed. The corneal surface may be described in a number of ways; some researchers have used conic sections while others have used more complex polynomial expressions. Computer algorithms have also been developed to calculate quantitative measures of corneal topography to augment the information obtained from topographical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…[4][5][6][7] Few studies have assessed the accuracy of corneal elevation data derived from the Pentacam system. One study 8 found that several parameters provided by this system were statistically correlated with suspected keratoconus based on Placido topography.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Few studies have assessed the accuracy of corneal elevation data derived from the Pentacam system. One study 8 found that several parameters provided by this system were statistically correlated with suspected keratoconus based on Placido topography.…”
Section: Discussionmentioning
confidence: 99%
“…These include keratometry, keratoscopy, computer-assisted videokeratography, and rasterstereography. [21][22][23] The Orbscan II topography system makes it possible to acquire in 1 examination information about the anterior and posterior corneal surfaces, corneal thickness over the whole corneal area, and anterior surface of the iris and lens as well as anterior chamber depth. 1 Therefore, it provides useful and predictable information for clinical applications to not only detect corneal diseases, such as keratoconus, 4 but also screen for glaucoma risk factors 24,25 or evaluations prior to implanting phakic intraocular lenses for the correction of myopia and hyperopia performing refractive surgical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…As is clearly documented by Fowler and Dave [12], there is a very wide variation in overall eye shape amongst the normal population. Provided that the corneal centre of radius does not approach the centre of rotation of the eye itself, it should be possible to deduce the point-of-regard even for eye shapes that deviate considerably from the norm.…”
Section: Further Workmentioning
confidence: 85%
“…In this section a more detailed mathematical description of the simulated system is presented, ending with the results of testing the system with and without the addition of noise. [12] and is idealised in the sense that it possesses perfect symmetry about the direction of gaze. The aspherical topography of the aver- Table 1.…”
Section: Simulation Of the Sensor Systemmentioning
confidence: 99%
See 1 more Smart Citation